THE ROLE OF EMPOWERING LEADERSHIP IN ENHANCING INNOVATIVE BEHAVIOR AMONG MILLENNIAL AND GENERATION Z IN THE HEALTHCARE SECTO - Aditya Ningrum, Raisa Endah; Anindita, Rina (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
In the high-stakes environment of regulated industries, the tension between strict compliance and the necessity for innovation creates a unique challenge for organizational leaders. Rather than acting as mere supervisors, modern leaders must serve as facilitators who empower their teams to navigate these boundaries with creative responsibility. This study investigates how an empowering leadership style fosters innovative behavior, specifically by examining the roles of psychological empowerment and knowledge sharing among 200 Millennial and Gen Z professionals in Indonesia's pharmaceutical and medical device sectors. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the analysis demonstrates that while leadership positively influences all studied variables, it is the internal sense of psychological empowerment rather than the formal exchange of information that acts as the primary catalyst for innovation. Surprisingly, generational differences proved to be an insignificant factor, as both cohorts adapt similarly to the industry's rigorous regulatory framework. Consequently, the findings suggest that organizations should move away from age-based management strategies and instead prioritize leadership practices that build the psychological confidence and autonomy of their employees to sustain long-term innovative growth.